Toxicity and genotoxicity of azaarenes using in vitro screening bioassays - Bartoš, Tomáš (2006)
N-heterocyclic polyaromatic hydrocarbons (NPAHs, azaarenes) have been of a major concern for several last years. Even if their environmental concentrations are lower than PAHs concentrations, they may play a significant role in both human and environmental risks. This study was focused on assessment of genotoxicity of 2-, 3-, 4- and 5-ringed NPAHs. In vitro tests Toxi-Chromotest, SOS-Chromotest and GreenScreen Essay were used for detection of the toxic and genotoxic effects. The results indicate that NPAHs have higher genotoxic potential than their homocyclic analogues. In addition to the determination of the toxic effects, a simple analysis of structure-toxicity relationships was performed. Based on the correlation analyses the significant relationship between the genotoxic activity of the genotoxic NPAHs and both structural descriptors affecting molecule transport through cellular membrane and electronic descriptors affecting reactivity were determined.